1994
DOI: 10.1039/c39940002731
|View full text |Cite
|
Sign up to set email alerts
|

Complexed bilayer membranes with novel structural features formed by amphiphiles of monoalkyl derivatives of ethylenediamine

Abstract: The CuN4 headgroups and the aliphatic tails in Cu*+-complexed bilayer membranes exhibit two-dimensional ordered orientations which can be classified into two types with different structural features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Good agreements can be found between the tail length dependence of the T c value of the complexed bilayer membranes in aqueous solutions through the DSC curves and that of the D n value of the cast films from the aqueous bilayers through the XRD measurements. Combining the results obtained via these two methods and our previous research, , it can be concluded that (1) the aggregate characteristics of this series of single-chain amphiphiles formed in aqueous dispersions are basically maintained in the immobilized films, i.e., the water-cast films, and (2) the complexed bilayer membranes formed by the amphiphiles hold two entirely different types of structures.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Good agreements can be found between the tail length dependence of the T c value of the complexed bilayer membranes in aqueous solutions through the DSC curves and that of the D n value of the cast films from the aqueous bilayers through the XRD measurements. Combining the results obtained via these two methods and our previous research, , it can be concluded that (1) the aggregate characteristics of this series of single-chain amphiphiles formed in aqueous dispersions are basically maintained in the immobilized films, i.e., the water-cast films, and (2) the complexed bilayer membranes formed by the amphiphiles hold two entirely different types of structures.…”
Section: Resultssupporting
confidence: 62%
“…Therefore it is seen that the headgroup structures will greatly influence the packing fashion of the hydrocarbon tails in the bilayer membranes. Combining the XRD analyses on the lamellar structure of the cast films, it can be deduced that when n = 8, the two spatially separated aliphatic chains extend obliquely into the tail gap of the neighboring amphiphiles in the same layer to form the tail-to-tail bilayer structure and the compressed tetrahedral CuN 4 lies along the membrane surface with its central plane vertical to the membrane normal; in the case of n = 12−18, the chains strongly interdigitate in the bilayer and tilt, so leading to a membrane thickness smaller than the monomolecular length of the corresponding amphiphile, and the CuN 4 coordination planes align along the membrane normal and parallel to each other . Therefore it is seen that the competition between the steric isomerization of the CuN 4 headgroups and the spontaneous assembly of the aliphatic tails result in the structural diversity in the novel complexed bilayer membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In our previous papers, we have reported that complexed bilayer membranes are formed from a series of single-chain amphiphiles C n H 2n+1 NHC 2 H 4 NH 2 dispersed in dilute aqueous Cu(NO 3 ) 2 . 6 In the present work, our investigation has been concentrated on the control of the organized structure of monoalkylethylenediamine in dilute aqueous CuX 2 by changing the counter ions (X 2 = Cl 2 , Br 2 , NO 3 2 and ClO 4 2 ). † Fig.…”
mentioning
confidence: 99%
“…Several groups have reported bilayer structures with copper(II) as counterions 12,13 including vesicular morphology; 12 also combinations of copper ions with chelating compounds, forming bilayer 14 or vesicle [15][16][17] structures, are known.…”
mentioning
confidence: 99%